Effect of conservation agriculture practices on productivity and sustainability of pigeonpea (Cajanus cajan)-wheat (Triticum aestivum) cropping system in Indo-Gangetic plains of India - SEPAT, SEEMA; SHARMA, A R; KUMAR, DINESH; DAS, T K (The Indian Journal of Agricultural Sciences, 2015)
A long term field experiment was conducted at Indian Agricultural Research Institute, New Delhi during 2008-09 to 2011-12 on a sandy loam soil to study the effect of tillage and crop establishment techniques, and residue management practices on pigeonpea (Cajanus cajan L.) - wheat (Triticum aestivum L.) cropping system. Results indicated that zero tillage-raised bed (ZT-B), zero tillage-flat bed (ZT-F) and conventional tillage-raised bed (CT-B) influenced pods/plant, spikes/m2 and grains/spike in pigeonpea and wheat crop. Grain yield of pigeonpea and wheat in zero tillage was 5.4 and 2.47 % higher over conventional tillage, respectively. ZT-F had higher system productivity, net returns and benefit:cost ratio, but ZT-B had higher wheat equivalent yield (WEY). Among all the practices, system yield and net returns were lowest in conventional tillage-flat bed (CT-F). Application of residue gave 14.32 and 34.39 % higher pigeonpea and wheat grain yield, respectively, over the no residue. System productivity, WEY and sustainable yield index (SYI) also increased in combined use of pigeonpea+wheat residue @ 3 tonnes/ha over no residue application. Zero tillage with combined application of residue @ 3 tonnes/ha improved productivity and sustainability of the system. Similar net returns were gained with pigeonpea + wheat residue @ 3 tonnes/ha (Rupees 84,500) and sole pigeonpea residue @ 3 tonnes/ha (Rupees 84 200) application, but net B:C ratio was higher with pigeonpea residue @ 3 tonnes/ha (2.68) than pigeonpea + wheat residue @ 3 tonnes/ha (2.55) application.